Hemorrhagic fever with renal syndrome：pathogenesis and clinical picture - Hong eJiang; Hong eDu; li mei eWang; Ping Zhong eWang; Xue Fan eBai (Frontiers in Cellular and Infection Microbiology, 2016)
Hantaan virus (HTNV) causes hemorrhagic fever with renal syndrome (HFRS), which is a zoonosis endemic in eastern Asia, especially in China. The reservoir host of HTNV is field mouse (Apodemus agraricus). The main manifestation of HFRS, including acute kidney injury, increases vascular permeability and coagulation abnormalities. In this paper, we review the current knowledge of the pathogenesis of HFRS including virus factor, immunity factor and host genetic factors. Furthermore, the treatment and prevention will be discussed.